2022
DOI: 10.1111/nph.18383
|View full text |Cite
|
Sign up to set email alerts
|

The additional PRC2 subunit and Sin3 histone deacetylase complex are required for the normal distribution of H3K27me3 occupancy and transcriptional silencing in Magnaporthe oryzae

Abstract: Development in higher organisms requires proper gene silencing, partially achieved through trimethylation of lysine 27 on histone H3 (H3K27me3). However, how the normal distribution of this modification is established and maintained and how it affects gene expression remains unclear, especially in fungi. Polycomb repressive complex 2 (PRC2) catalyses H3K27me3 to assemble transcriptionally repressed facultative heterochromatin and is crucial in animals, plants, and fungi.Here, we report on the critical role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…In M. oryzae , autophagy is required for the degradation of the conidial components during appressorium formation ( 3 , 29 ). In our previous study, Sin3 was found to function primarily as a globally transcriptional repressor in M. oryzae ( 40 ). By analyzing the transcriptome sequencing (RNA-seq) data, we noted that expression levels of extensive autophagy-related genes ( ATGs ) were significantly upregulated in the Δ sin3 strain compared with those in the wild-type (WT) strain, which included ATG1 , ATG3 , ATG4 , ATG8 , ATG9 , ATG11 , ATG12 , ATG13 , ATG14 , ATG15 , ATG16 , ATG17 , ATG23 , ATG24 , ATG27 , ATG26 , and ATG29 (see Fig.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…In M. oryzae , autophagy is required for the degradation of the conidial components during appressorium formation ( 3 , 29 ). In our previous study, Sin3 was found to function primarily as a globally transcriptional repressor in M. oryzae ( 40 ). By analyzing the transcriptome sequencing (RNA-seq) data, we noted that expression levels of extensive autophagy-related genes ( ATGs ) were significantly upregulated in the Δ sin3 strain compared with those in the wild-type (WT) strain, which included ATG1 , ATG3 , ATG4 , ATG8 , ATG9 , ATG11 , ATG12 , ATG13 , ATG14 , ATG15 , ATG16 , ATG17 , ATG23 , ATG24 , ATG27 , ATG26 , and ATG29 (see Fig.…”
Section: Resultsmentioning
confidence: 95%
“…One layer is regulating the transcriptional expression of target genes at the transcriptional level and the other is regulating the acetylation of the target protein at the posttranslational level ( 41 ). In our recent study, the global level of acetylation of histone H4 lysine 16 (H4K16ac), which has been reported to be involved in the regulation of autophagy ( 6 ), was increased in the Δ sin3 strain ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations